2010
DOI: 10.1242/dev.051052
|View full text |Cite
|
Sign up to set email alerts
|

An SNP in an ultraconserved regulatory element affects Dlx5/Dlx6 regulation in the forebrain

Abstract: SUMMARYDlx homeobox genes play a crucial role in the migration and differentiation of the subpallial precursor cells that give rise to various subtypes of -aminobutyric acid (GABA)-expressing neurons of the forebrain, including local-circuit cortical interneurons. Aberrant development of GABAergic interneurons has been linked to several neurodevelopmental disorders, including epilepsy, schizophrenia, Rett syndrome and autism. Here, we report in mice that a single-nucleotide polymorphism (SNP) found in an auti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 56 publications
1
77
0
Order By: Relevance
“…We also observed that once a complex with DNA was formed, Dlx5 was more stable and that we could cleave GB1 from the DNA-bound Dlx5 before starting crystallization trials. A 21 bp DNA sequence, AAATGCAGCCA TAAT TAGAGT, had previously been identified to target expression of the Dlx5/Dlx6 bi-gene cluster to the developing forebrain in mice [24]. This sequence includes the TAAT motif typically recognized by homeodomains, including all six Dlx proteins [25].…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that once a complex with DNA was formed, Dlx5 was more stable and that we could cleave GB1 from the DNA-bound Dlx5 before starting crystallization trials. A 21 bp DNA sequence, AAATGCAGCCA TAAT TAGAGT, had previously been identified to target expression of the Dlx5/Dlx6 bi-gene cluster to the developing forebrain in mice [24]. This sequence includes the TAAT motif typically recognized by homeodomains, including all six Dlx proteins [25].…”
Section: Resultsmentioning
confidence: 99%
“…The biological significance of Evf2-Dlx5/6ei interactions is supported by altered adult hippocampal GABA circuitry in mice lacking Evf2 (Bond et al, 2009), transcriptional effects of a single nucleotide polymorphism (SNP) in Dlx5/6ei linked to autism (Poitras et al, 2010), and the established role of MECP2 in autism (Guy et al, 2007;Guy et al, 2001). Loss of Evf2 results in increased Dlx5 and Dlx6 expression in E13.5 MGE, a major site of sonic hedgehog-activated Dlx and Evf2 gene regulatory events crucial for GABAergic interneuron development (Anderson et al, 1997a;Feng et al, 2006;Kohtz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dlx1/2 antagonize MECP2 repression of Dlx5 (Berghoff et al, 2013). A Dlx5/6 ei SNP that disrupts DLX1/2 binding was identified in an autistic proband (Poitras et al, 2010). Given the global DNA-binding properties of MECP2, it has been difficult to envision how this may cause such specific neurological phenotypes, as in Rett syndrome.…”
mentioning
confidence: 99%